Enhancing the adhesion and tribological performance of Si-DLC film on NBR by Ar plasma pretreatment under a high bias - Li Qiang; Changning Bai; Aimin Liang; Junyan Zhang (AIP Advances, 2019)
Silicon-containing diamond-like carbon (Si-DLC) films were successfully deposited on nitrile-butadiene rubber (NBR) via magnetron sputtering Si target in Ar and CH4 mixture atmosphere. The influence of Ar plasma pretreatment bias on the adhesion and tribological properties of the Si-DLC coated NBR were investigated systematically. The results indicated that the surface roughness of NBR substrate decreased monotonously with the increase of bias. Compared with the virgin NBR, the surface topography did not change significantly under a low bias, but a shallow layer and considerable chain scission could be observed by SEM and FTIR analysis under a high bias. As a consequence, the excellent adhesion could be obtained by Ar plasma pretreatment under a high bias (>-500 V), while the adhesion of the samples pretreated by a low bias (≤-500 V) were even worse than that of untreated samples. Furthermore, the samples pretreated at a relatively high bias of -1000 V exhibited the lowest and stable friction coefficient of 0.25 and outstanding wear resistance, while the tribological performance of the samples pretreated with a low bias (≤-500V) were even worse than that of untreated ones. The research results of this work are of great surface engineering significance for the design and fabrication of hard films with a high adhesion and excellent tribological performance on rubber substrates.